Task-Based Training Materials For Ecotourism - Miangtari, Nyoman; Tantra, Dewa Komang; Ratminingsih, Ni Made (JPI (Jurnal Pendidikan Indonesia), 2017)
This study aimed at developing training materials for ecotourism at Sambangan village.This research was a research and development using modified Borg and Gall design (2003). There were some steps conducted in order to develop the training materials namely; need analysis, design first draft, expert judgment, revision I, field test, revision II, and final product. There were four instruments applied to obtain the research data, observation, document study, questionnaire, and interview guide. The findings were described descriptively. The results of this study found that (i) the tour guides needed tasks-based training materials that could improve their speaking skill, (ii) developed training materials based on tasks of the members of kelompok sadar wisata had been evaluated as excellent materials, (iii) The developed training materials was readable, implementable, and measurable